Vertical Licensing, Input Pricing, and Entry - Elpiniki Bakaouka; Chrysovalantou Milliou (Center for Economic Studies and ifo Institute (CESifo), 2017)
We explore the incentives of a vertically integrated incumbent firm to license the production technology of its core input to an external firm, transforming the licensee into its input supplier. We find that the incumbent opts for licensing even when licensing also transforms the licensee into one of its direct competitors in the final products market. In fact, the licensee's entry into the final products market, although increases the competition and the cost that the licensor faces, it reinforces, instead of weakens, the licensing incentives. Furthermore, the licensee's entry augments the positive welfare implications of vertical licensing.
Keywords: L22; L24; L13; L42; D45; 330; licensing; vertical relations; entry; two-part tariffs; outsourcing